2017
DOI: 10.4103/1947-489x.210115
|View full text |Cite
|
Sign up to set email alerts
|

Hematological profile of patients with type 2 diabetic mellitus in El-Beida, Libya

Abstract: Objectives: The objective of this study is to help identify the hematological profile of patients with diabetes Settings: The study was conducted at El-Beida Hospital, El-Beida City, Libya. Subjects and Methods: The study subjects selected for this study consist of 103 Libyan type 2 diabetic patients (79 males + 24 females) and 39 healthy non-diabetic subjects (29 males and 10 females) acted as controls. They were matched for age (56.1 ± 7.8 years vs. 55.0 ± 6.3 years. The hematoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 20 publications
3
4
1
Order By: Relevance
“…41 In the present study, WBC indices (WBC count, lymphocyte, and mixed number) increased significantly in the DM patients compared with the control group. This study supports the finding of previous studies conducted in Libya, 42 Ethiopia, 43 India, 44 Nigeria, 45 Bangladesh, 46 and Turkey. Alteration in WBC indices has also been reported in DM patients.…”
Section: Discussionsupporting
confidence: 92%
“…41 In the present study, WBC indices (WBC count, lymphocyte, and mixed number) increased significantly in the DM patients compared with the control group. This study supports the finding of previous studies conducted in Libya, 42 Ethiopia, 43 India, 44 Nigeria, 45 Bangladesh, 46 and Turkey. Alteration in WBC indices has also been reported in DM patients.…”
Section: Discussionsupporting
confidence: 92%
“…The mean RBC count, Hct, and Hgb values were significantly lower in T2DM patients than in the control group. This finding is in harmony with reports from India, 28 Libya, 29 Sudan, 30 and Ethiopia. 20 , 21 The relative decrease in RBCs count, Hct, and Hgb level might be that long-term hyperglycemia causes the generation of free oxygen radicals and irreversible glycation of hemoglobin and RBC membrane proteins.…”
Section: Discussionsupporting
confidence: 90%
“…Patients and controls were well matched for age and gender distribution. 12 Present study showed that diabetics had mean hemoglobin of 11.17±4.42 (g/dl) and non-diabetics 14.11±3.46 (g/dl). In diabetics mean haemoglobin, RBCs, PCV, and MCV was significantly lower than in nondiabetics.…”
Section: Discussionmentioning
confidence: 46%
“…Similar observations were made by Al Salhen KS et al in T2DM had lower haemoglobin concentrations. 12 In T2DM patient's PCV, whole blood haemoglobin, RBCs and MCV values were significantly lower than in controls with percent differences of 27.7, 19.2, 23.5 and 5.4%, respectively. The mean values for MCHC and MCH were also significantly greater in diabetic patients than healthy controls.…”
Section: Discussionmentioning
confidence: 75%